PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA IV MEDAN - Jenni Tarigan; Mitaria Mitaria (JURNAL ILMIAH SOCIO SECRETUM, 2020)
The staffs’ performance in an organization cannot be separated from the existence of motivation. Motivation is an individual’s personal condition to give support to the individual to do certain activities to reach some goals. Staff’s motivation can be done by adjusting the personal’s goals with the organization’s goals. Maximizing the staffs’ motivation in reaching the organization’s goals was the main judgement of performance. The problem analyzed in this research was whether motivation had effect on staffs’ performance in PT Perkebunan Nusantara IV Medan. The sample of this research was as many as 100 individuals. Instruments of data collecting were observation, documentation, interview and questionnaire. The method of data analysis was simple linear regression method with t test and determination coefficient test as the hypothesis test. The result of the study showed that motivation had effect on staffs’ performance. This was proven with the equity of simple linear regression obtained was Y= 8.386 + 0.616X and the value t calculation ( 8.195) and the value of t table ( 6.313) and the value of significance obtained was 0.000 < 0.05. The results of the study showed that the relation between motivation with staffs’ performance in PT. Perkebunan Nusantara IV Medan was categorized as strong ( R = 0.638), the value of determination coefficient (R2) obtained was 0. 407. This showed that 40.7 % of performance (Y) was affected by independent variable, which was motivation (X). Meanwhile the rest, as much as 59.3 %, was affected by other variables which were not analyzed. It was suggested that the management of PT. Perkebunan Nusantara IV Medan could increase motivating the staffs so that the staffs’ performance achieved could be maximized.